Sleep/wake behaviours of elite athletes from individual and team sports - Lastella, M.; Roach, G. D.; Halson, S. L.; Sargent, C. (European Journal of Sport Science, 2015)
Sleep is an essential component for athlete recovery due to its physiological and psychological restorative effects, yet few studies have explored the habitual sleep/wake behaviour of elite athletes. The aims of the present study were to investigate the habitual sleep/wake behaviour of elite athletes, and to compare the differences in sleep between athletes from individual and team sports. A total of 124 (104 male, 20 female) elite athletes (mean ± s: age 22.2 ± 3.0 years) from five individual sports and four team sports participated in this study. Participants` sleep/wake behaviour was assessed using self-report sleep diaries and wrist activity monitors for a minimum of seven nights (range 7-28 nights) during a typical training phase. Mixed-effects analyses of variances were conducted to compare the differences in the sleep/wake behaviour of athletes from two sport types (i.e. individual and team). Overall, this sample of athletes went to bed at 22:59 ± 1.3, woke up at 07:15 ± 1.2 and obtained 6.8 ± 1.1 h of sleep per night. Athletes from individual sports went to bed earlier, woke up earlier and obtained less sleep (individual vs team; 6.5 vs 7.0 h) than athletes from team sports. These data indicate that athletes obtain well below the recommended 8 h of sleep per night, with shorter sleep durations existing among athletes from individual sports.